2017
DOI: 10.1097/iyc.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Newborn Behavioral Observations (NBO) System on Sensitivity in Mother–Infant Interactions

Abstract: The Newborn Behavioral Observations (NBO) system is a neurobehavioral observation tool designed to sensitize parents to infants' capacities and individuality and to enhance the parent–infant relationship by strengthening parents' confidence and practical skills in caring for their children. The NBO's focus on relationship building is intended for infant mental health professionals who strive for a relational, family-centered model of care versus a pathology-based model. This study assessed the impact of the NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 36 publications
0
46
5
Order By: Relevance
“…The results from the mother-infant relationship domain did not support our hypothesis that the NBO would be associated with higher levels of maternal bonding, re ective functioning and con dence. Thus, our results were not in line with earlier research indicating that the NBO can signi cantly increase maternal engagement (40), con dence (43) and maternal sensitivity (41). However, the present study did not include any observational measures of actual mother-infant interaction, which could possibly have shed additional light on this issue.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The results from the mother-infant relationship domain did not support our hypothesis that the NBO would be associated with higher levels of maternal bonding, re ective functioning and con dence. Thus, our results were not in line with earlier research indicating that the NBO can signi cantly increase maternal engagement (40), con dence (43) and maternal sensitivity (41). However, the present study did not include any observational measures of actual mother-infant interaction, which could possibly have shed additional light on this issue.…”
Section: Discussioncontrasting
confidence: 97%
“…There is a possibility that the high functioning of this sample did not give much room for signi cant enhancement by receiving the NBO, neither on the depressive symptoms/parental stress domain nor on the mother infant relationship domain. Two previous studies of NBO conducted in the US with a more limited sample size have indicated that the intervention may have bene cial effect by reducing the odds of depression in rst-time mothers (42) and increasing sensitivity in mother-infant interactions (41). Contrary to this, our results suggest that the bene ts of the NBO on depressive symptoms, parenting stress and measures related to the mother-infant relationship may be limited within a general population sample with particularly well-functioning participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes observations of responsivity to visual and auditory stimulation, capacity for habituation or sleep protection, amount of crying and ease of consoling, stress responses, reflexes, muscle tone and motor activity. Based on the observations, care giving strategies such as handling, sleep protection, comforting and regulation of social interaction are discussed (41). The NBO takes 15 to 40 minutes to administer and can be used from birth until the infant is three months old.…”
Section: The Interventionmentioning
confidence: 99%